Transforming Nature of Collaborative Work Environments : From Open-planned Flexible Offices and Coworking Spaces to the Digitalised Work Alternatives - Orel, Marko, 1986-; Mariotti, Ilaria; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This habilitation thesis explores the impact of the growing trend of open-plan flexible offices and coworking spaces on knowledge workers' performance, wellbeing, and collaborative capacity. Through a comprehensive review of the current research, the literature on open-plan offices reveals a gradual preference for closed office layouts, driven primarily by traditional open-plan offices with fixed desks. To effectively understand the success of open-plan offices, it is critical to consider factors such as the characteristics of participants, office layout, and other outcome variables. Furthermore, the study of coworking spaces highlights the significance of understanding the wants and needs of users, as well as the influence of ambiance and spatial design in fostering user interactions and collaboration. The thesis also examines the advantages of coworking spaces for working parents and businesses seeking to attract and retain talent. The motivations for using these spaces differ among countries, with professionals in the Netherlands prioritizing flexibility, those in Germany emphasizing affordability and professional appearance, and those in the Czech Republic placing a greater emphasis on supportive services. The habilitation thesis concludes by stressing the need for further research to fully understand the impact of open-plan flexible offices and coworking spaces on worker performance and wellbeing, as well as the implications of the digitalization trend and its potential hybridization or gradual replacement of physical workspaces. This body of work presents a comprehensive view of the rapidly changing workplace landscape and its impact on all stakeholders.
Vedoucí práce
Habilitační práce (doc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet